2019
DOI: 10.1002/open.201900150
|View full text |Cite
|
Sign up to set email alerts
|

Ortho‐Quinone Methide Driven Synthesis of New O,N‐ or N,N‐Heterocycles

Abstract: To synthesize functionalized Mannich bases that can serve two different types of ortho ‐quinone methide ( o ‐QM) intermediates, 2‐naphthol and 6‐hydroxyquinoline were reacted with salicylic aldehyde in the presence of morpholine. The Mannich bases that can form o ‐QM and aza ‐ o ‐QM were also synthesized by mixing 2‐naphthol, 2‐nitrobenzaldehyde, and morpholine followed by reduction of the nitro g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(95 reference statements)
1
3
0
Order By: Relevance
“…In analogy to previous investigations [25] and to the results of the structural analyses of 14-16 (vide supra), reactions starting from 21, in all cases, yielded trans isomers 24a, 26a, and 28a. Their NMR spectra are akin to the corresponding spectra of the compounds without an OH group at position 2′ (14)(15)(16) and to compounds having a naphthalene moiety instead of phenanthrene [25].…”
Section: Detailed Nmr Analysis Of New Phenanthr[910-e]oxazines 27absupporting
confidence: 60%
See 1 more Smart Citation
“…In analogy to previous investigations [25] and to the results of the structural analyses of 14-16 (vide supra), reactions starting from 21, in all cases, yielded trans isomers 24a, 26a, and 28a. Their NMR spectra are akin to the corresponding spectra of the compounds without an OH group at position 2′ (14)(15)(16) and to compounds having a naphthalene moiety instead of phenanthrene [25].…”
Section: Detailed Nmr Analysis Of New Phenanthr[910-e]oxazines 27absupporting
confidence: 60%
“…The reactive moiety thus formed can be stabilized by reactions with different dienophiles [14,21,22] or it can participate in [4 + 2] cycloadditions with cyclic imines to form new heterocycles [18,23,24]. Very recently the transformation of functionalised 1-aminobenzyl-2-naphthols via [4 + 2] cycloaddition has been examined [25]. It was found that the regio-and diastereoselectivity of the cycloaddition depend on the functional group of the phenyl substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, readily available aminonaphthol/aminophenol (Betti base) derivatives were chosen as the substrate to investigate the sequential C−N bond cleavage and C−S bond forming reactions. It was presumed that the use of aminonaphthol/aminophenol derivatives as the substrate would result in the formation of the in situ generated ortho ‐quinone methide intermediates [28,29] which on subsequent reaction with thiol would produce the desired thioether derivatives. Hence, both aminonaphthol and aminophenol derivatives 1 a – 1 d were chosen as a model substrates to screen the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the significance of these valuable compounds, many efforts have been made in the construction of benzoacridine derivatives. However, most of the early synthesis methods require highly functionalized precursors or multi‐step procedures [11–16] . The general methods for the synthesis of benzoacridines can mainly be classified into three categories.…”
Section: Introductionmentioning
confidence: 99%